2019
DOI: 10.4193/rhin19.085
|View full text |Cite
|
Sign up to set email alerts
|

What drives depression in empty nose syndrome? A Sinonasal Outcome Test-25 subdomain analysis

Abstract: Background: Empty nose syndrome (ENS) is a debilitating disorder characterised by paradoxical nasal obstruction after excessive surgical excision of nasal tissues. ENS negatively impacts the quality of life (QOL) and psychological status of patients. This study aimed to determine the associations among disease-specific QOL impairments and the severity of anxiety and depression before and after surgery in ENS patients. Methods: A total of 68 ENS patients were prospectively recruited and underwent submucosal Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(84 citation statements)
references
References 16 publications
6
78
0
Order By: Relevance
“…As a result, we suggest the importance of evaluating these ENS patients with SNOT‐25, which included six domains of rhinogenic symptoms, extra‐nasal rhinological symptoms, ear/facial symptoms, sleep dysfunction, psychological dysfunction, and empty nose symptoms. Previous studies by Jiang et al and our cohort also demonstrated the utility of SNOT‐25 as a measurement tool for patients with ENS 8,14 . However, diagnosis of ENS may require a subjective nasal obstruction and a paradoxical findings of patent nasal airway on objective endoscopic evaluation, as well as evaluation of the response to intervention, using the cotton test or other suitable methods 10…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…As a result, we suggest the importance of evaluating these ENS patients with SNOT‐25, which included six domains of rhinogenic symptoms, extra‐nasal rhinological symptoms, ear/facial symptoms, sleep dysfunction, psychological dysfunction, and empty nose symptoms. Previous studies by Jiang et al and our cohort also demonstrated the utility of SNOT‐25 as a measurement tool for patients with ENS 8,14 . However, diagnosis of ENS may require a subjective nasal obstruction and a paradoxical findings of patent nasal airway on objective endoscopic evaluation, as well as evaluation of the response to intervention, using the cotton test or other suitable methods 10…”
Section: Discussionsupporting
confidence: 52%
“…Lemogne et al also reported the successful management of an ENS patient with anxiety and depression by cognitive behavior therapy and a serotonin reuptake inhibitor 25 . Our previous studies reported a high prevalence of depression and anxiety among ENS patients and the effectiveness of surgical treatment with submucosal implantation 13,14 . Furthermore, ENS symptoms are associated with psychological burden and could be good predictors of moderate‐to‐severe depression 14 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations